HUMAN DEVELOPMENT IN VIETNAM: THE EFFECTS OF ECONOMIC GROWTH AND CARBON DIOXIDE EMISSIONS (Isagoge - Journal of Humanities and Social Sciences, 2026)
Vietnam’s economy has grown strongly over the past decades, while environmental pollution has increased at the same time. This situation makes sustainable human development an important concern for the country. The study examines the relationship between economic growth, carbon dioxide emissions, foreign direct investment, and the Human Development Index (HDI) over the period 1990–2023. The data come from the World Bank and UNDP, and the ARDL model is applied in the analysis. The cointegration test confirms a long-run relationship among the variables. Economic growth, measured by GDP, has a positive effect on the Human Development Index. However, GDP squared has a negative coefficient. This shows that when income becomes higher, its positive contribution to welfare becomes smaller. Carbon dioxide emissions lower human development in the long run, while foreign direct investment does not have a statistically significant effect. These findings mean that Vietnam should improve the quality of economic growth, control emissions more effectively, and select investment projects more carefully to achieve sustainable development.